Study of high-transverse-momentum higgs boson production in association with a vector boson in the qqbb final state with the ATLAS Detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Mkrtchyan, Tigran; Rassloff, Damir Fabrice; Sauer, Christof; Schöning, André; Schultz-Coulon, Hans-Christian; et al. (Physical review letters, 2024)
This Letter presents the first study of Higgs boson production in association with a vector boson (𝑉 =𝑊 or 𝑍) in the fully hadronic 𝑞⁢𝑞⁢𝑏⁢𝑏 final state using data recorded by the ATLAS detector at the LHC in proton-proton collisions at √𝑠=13 TeV and corresponding to an integrated luminosity of 137 fb−1. The vector bosons and Higgs bosons are each reconstructed as large-radius jets and tagged using jet substructure techniques. Dedicated tagging algorithms exploiting 𝑏-tagging properties are used to identify jets consistent with Higgs bosons decaying into 𝑏⁢¯𝑏. Dominant backgrounds from multijet production are determined directly from the data, and a likelihood fit to the jet mass distribution of Higgs boson candidates is used to extract the number of signal events. The 𝑉⁢𝐻 production cross section is measured inclusively and differentially in several ranges of Higgs boson transverse momentum: 250-450, 450-650, and greater than 650 GeV. The inclusive signal yield relative to the standard model expectation is observed to be 𝜇=1.4+1.0−0.9 and the corresponding cross section is 3.1±1.3⁢(stat)+1.8−1.4⁢(syst) pb.